2012
DOI: 10.1105/tpc.112.100339
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analyses of the Plant Photosystem I–Light-Harvesting Complex II Supercomplex Reveal That Light-Harvesting Complex II Loosely Bound to Photosystem II Is a Very Efficient Antenna for Photosystem I in State II

Abstract: State transitions are an important photosynthetic short-term response that allows energy distribution balancing between photosystems I (PSI) and II (PSII). In plants when PSII is preferentially excited compared with PSI (State II), part of the major light-harvesting complex LHCII migrates to PSI to form a PSI-LHCII supercomplex. So far, little is known about this complex, mainly due to purification problems. Here, a stable PSI-LHCII supercomplex is purified from Arabidopsis thaliana and maize (Zea mays) plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
228
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(264 citation statements)
references
References 76 publications
32
228
4
Order By: Relevance
“…These data are consistent with the behaviour of npq4ch1 that lacks Chlb, and is thus devoid of all LHCs [37,38]; the slow phase of NPQ relaxation was found to be independent of LHC composition, indeed qM amplitude was similar in npq4 and npq4ch1 mutants ( figure 3e and table 2). State transitions lead to quenching of LHCII fluorescence by PSI [39] upon phosphorylation of LHCII, by STN7 kinase, driving its migration from PSII to PSI [40]; by using the mutant npq4stn7, we checked the possibility that state transition were involved in qM. The maximal amplitude of NPQ in npq4stn7 was essentially the same as in npq4 plants (figure 3f).…”
Section: (C) Role Of Xanthophyll Compositionmentioning
confidence: 99%
“…These data are consistent with the behaviour of npq4ch1 that lacks Chlb, and is thus devoid of all LHCs [37,38]; the slow phase of NPQ relaxation was found to be independent of LHC composition, indeed qM amplitude was similar in npq4 and npq4ch1 mutants ( figure 3e and table 2). State transitions lead to quenching of LHCII fluorescence by PSI [39] upon phosphorylation of LHCII, by STN7 kinase, driving its migration from PSII to PSI [40]; by using the mutant npq4stn7, we checked the possibility that state transition were involved in qM. The maximal amplitude of NPQ in npq4stn7 was essentially the same as in npq4 plants (figure 3f).…”
Section: (C) Role Of Xanthophyll Compositionmentioning
confidence: 99%
“…Previous reports have shown that the relative phosphorylation of Lhcb1 and Lhcb2 isoforms differs among thylakoid supercomplexes (Galka et al, 2012;Leoni et al, 2013). Here, we address the specific roles of Lhcb1 and Lhcb2 phosphorylation in photosynthetic acclimation.…”
mentioning
confidence: 99%
“…The PSI-LHCII complex assembles in state 2 and involves the binding of a mobile trimer, which contains Lhcb1 and Lhcb2 (Galka et al, 2012), to the PSI complex. This association depends on the kinase STN7.…”
Section: Antenna Phosphorylation In the Psi-lhcii State Transition Sumentioning
confidence: 99%
See 2 more Smart Citations